Hubungan dukungan keluarga dengan kualitas hidup lansia penderita diabetes mellitus - Blegur, Elentina; Tandilangi, Abigail Asfas (Holistik Jurnal Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a chronic disease that affects the quality of life of the elderly, especially if not managed properly. Family support is considered an important factor in helping elderly DM undergo treatment and adapt to a healthy life. Purpose: To determine the relationship between family support and the quality of life of elderly people with diabetes mellitus. Method: Quantitative research with a cross-sectional approach. The study sample consisted of 78 elderly people selected using a purposive sampling technique. Data were collected using the Hensarling Diabetes Family Support Scale (HFSS) questionnaire for family support and Diabetes Quality of Life (DQOL) for quality of life. Results: Showed that 100% of respondents had a high quality of life and 97.4% had high family support. However, statistical tests showed no significant relationship between family support and the quality of life of respondents (p-value 0.200; r = 0.223). Conclusion: There was no relationship between family support and quality of life in DM respondents. Suggestion: Health services can provide education to patient families regarding the importance of family support in improving the quality of life, especially for elderly people with DM, as well as forming support groups for the elderly.   Keywords: Diabetes Mellitus; Elderly; Family Support; Quality of Life.   Pendahuluan: Diabetes melitus (DM) merupakan penyakit kronis yang memengaruhi kualitas hidup lansia, terutama jika tidak dikelola dengan baik. Dukungan keluarga dianggap sebagai faktor penting dalam membantu lansia DM menjalani pengobatan dan beradaptasi dengan kehidupan yang sehat. Tujuan: Untuk mengetahui hubungan antara dukungan keluarga dengan kualitas hidup lansia diabetes melitus. Metode: Penelitian kuantitatif dengan pendekatan cross sectional. Sampel penelitian berjumlah 78 lansia yang dipilih dengan teknik purposive sampling. Data dikumpulkan dengan menggunakan kuesioner Hensarling Diabetes Family Support Scale (HFSS) untuk dukungan keluarga dan Diabetes Quality of Life (DQOL) untuk kualitas hidup. Hasil: Menunjukkan bahwa 100% responden memiliki kualitas hidup yang tinggi dan 97.4% memiliki dukungan keluarga yang tinggi. Namun, uji statistik menunjukkan tidak ada hubungan yang signifikan antara dukungan keluarga dengan kualitas hidup responden (p-value=0.200; r=0.223). Simpulan: Tidak terdapat hubungan antara dukungan keluarga dengan kualitas hidup pada responden DM. Saran: Layanan kesehatan dapat memberikan edukasi kepada keluarga pasien mengenai pentingnya dukungan keluarga terhadap peningkatan kualitas hidup, khususnya bagi lansia penderita DM sekaligus membentuk kelompok pendukung bagi lansia.   Kata Kunci: Diabetes Melitus; Dukungan Keluarga; Kualitas Hidup; Lansia.